ANALISIS PERAN PERCEIVED ORGANIZATIONAL SUPPORT DAN TRANSFORMATIONAL LEADERSHIP TERHADAP PENURUNAN TURNOVER KARYAWAN - Marina, Lela; Wikaningrum, Tri (Postgraduate Management Journal, 2026)
This study aims to explain the causal relationship between the variables studied, namely Perceived Organizational Support, Transformational Leadership, Affective Commitment, and Turnover Intention. The type of research used is quantitative research design with a descriptive approach. The purpose of this approach is to explain the causal relationship between the variables studied. The research was conducted through a survey by distributing questionnaires to employees of three Hotel Grandhika Indonesia units: Hotel Grandhika Pemuda Semarang, Hotel Grandhika Iskandarsyah Jakarta, and Hotel Grandhika Setiabudi Medan as respondents. The data obtained were analyzed using inferential statistical techniques to test the formulated hypotheses and answer the questions in this study. The results of the study are stated that the Perceived Organizational Support and Transformational Leadership have a significantly positive effect on Affective Commitment. Perceived Organizational Support variable has a significant positive effect on Turnover Intention, however Transformational Leadership variable does not have a significant effect on Turnover Intention. Affective Commitment variable cannot mediate the relationship between Perceived Organizational Support and Transformational Leadership with Turnover Intention. This means that at Hotel Grandhika Indonesia there are other variables besides Affective Commitment that may mediate, or for the Perceived Organizational Support variable does not require a mediator. Meanwhile, for the Transformational Leadership variable, it is necessary to re-analyze the variables that can mediate, for example Employee Engagement.